Studi Tentang Pengaruh Penggunaan Teknologi dan Sistem Informasi, Sistem Manajemen Mutu, dan Budaya Organisasi Terhadap Kinerja Manajemen Perguruan Tinggi Swasta: Studi Kasus Universitas Bina Nusantara - Harjanto Prabowo; Bahtiar Saleh Abbas; Meyliana Meyliana (Bina Nusantara University, 2004)
Article discusses factors that influences college management performance, those are technology and information system, quality management system, and organization culture. The research is done by using Pearson correlation method, linear regression, and Customer Satisfaction Index (CSI) using cartesius diagram. Based on correlation test, there are only two out of three variables having significance correlation with performance management, that are quality management system and organization culture.